A group based smoking cessation pilot programme for community mental health clients in Sydney. (28th August 2013) - Devine, Erin; Khan, Raquiba Jahan; Bedford, Karen; Jiang, Wei Zhuang; Lim, Henry
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction: This article describes the process and evaluation of a smoking cessation support programme for mental health clients in Sydney. Aim: The objective of the study was to assess a group-based smoking cessation support model for community mental health clients. Methods: Two community mental health services participated; 29 clients received free NRT products and weekly education for 12 weeks on: effects of smoking, nicotine dependence, NRT use, withdrawal process and the benefits of quitting. Evaluation included face-to-face interviews, telephone or postal survey using a semi-structured questionnaire. Results: The baseline (n = 29) and follow-up (n = 14) surveys showed reduction in the number of cigarettes (30 to 21) smoked a day (55% vs. 36%). At one month 47% (n = 19) were confident about stopping smoking permanently whereas 19% (n = 14) reported the same after six months. Participants reported concerns of health effects, illness, physical symptoms (77% n = 27) and financial cost (93% n = 27) were the motivating factors in quitting. None of the findings was statistically significant. Conclusions: Community based interventions to address the rate of smoking in this group is needed. Financial and health benefits can be used as motivating factors, and integration of smoking cessation assistance in treatment and rehabilitation of mental health consumers would be useful.